Isolation, characterization and screening of rhizospheric bacteria of Pittosferum resiniferum Hemsl. - Hanirah, R; Piakong Mohd Tuah; Syaufi, L (2015)
The bacterial rhizosphere species of host plant, Petroleum Nut (Pittosferum resiniferum) were isolated and characterized morphologically. The isolates were designated as, TSArp- Cr2, TSArp- Cr3, TSArp- Cr4, TSArp- Cr5, TSArp- Cr6 and TSArp- Cr7. All of the species were tested on three different concentration of phenol (1mM, 3mM and 5mM). Only species TSArp- Cr4 and TSArp- Cr6 growth were detected. The highest growth is 6Log10CFU/ml in 1mM by TSA-Cr4. The lowest reading was 3.6 Log10CFU/ml in 3mM by TSA-Cr6. Species TSArp- Cr4 has higher tolerance on phenol compared to TSArp- Cr6